A Green and Eco-Friendly Novel Retrieval Nife2o4@P-Doped G-C3n4 Nanorod Photocatalyst for Effective Removal of Tetracycline Antibiotics and Various Textile Dyes - Herrera-Diaz, F; Herrera-Diaz, F (Elsevier B.V., 2025)
Photocatalysts have inadequate practical use due to their low recyclability and inefficient use of photo-induced charge carriers. The fabrication process involved the incorporation of phosphorous-doped g-C3N4 with NiFe2O4 nanorods, utilizing an eco-friendly green synthesis method derived from Hibiscus rosasinensis extract. The synthesised samples were examined using XRD, FESEM, TEM, UV, and PL techniques to determine their crystal structure, shape, microscopic components, and characteristics. The XRD results indicate that NiFe2O4 exhibits a cubic structure characterized by nanocrystals. The FESEM images reveal that the NiFe2O4@P-g-C3N4 (NFO@P-g-CN) composite displays a nanorod structures with an average diameter of 20–25 nm and lengths extending to several micrometres. The catalyst made of NFO@P-g-CN showed improved TC (Tetracycline) degradation performance, with a noteworthy high rate constant of 0.0786 min−1 and a 98.6 % degradation rate in 60 min when exposed to visible light. This degradation rate is 3.15 times higher than that of pure NFO. The enhanced photocatalytic performance was attributed to the combined effects of P@g-CN and NFO, which resulted in a reduced band gap, increased surface area, and superior redox potential. The NFO@P-gCN photocatalyst was also evaluated with various organic dyes, including methylene blue (MB) and Malachite green (MG), under the same experimental conditions. The electrochemical behavior of the samples was also assessed through photo response and EIS monitoring. This study has the potential to pave the way for innovative designs of additional NFO-based systems utilizing g-C3N4 nanosheets for the purpose of removing pollutants from wastewater. © 2025 Elsevier B.V.